TO ASSESS THE CONDITION OF THE MYOCARDIUM IN PATIENTS CHRONIC HEART FAILURE ON THE BACKGROUND OF RHEUMATOID ARTHRITIS - Khusainova Munira Alisherovna; G’aniyev Akbar Abdirasulovich; Ziyotov Maqsud Baxtiyorovich; Narzullayev Javohir Anvarovich (Journals Park Publishing, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease of unknown etiology characterized by chronic erosive arthritis and systemic inflammatory damage to internal organs. The prevalence of RA is 0.5—2%. The peak of the onset of the disease occurs at the age of 30 to 55 years. Researchers' interest in comorbid conditions in RA is due to their influence on the course and prognosis of the disease itself, the choice of treatment tactics and on the quality of life of patients. Concomitant diseases may appear before the development of RA, during the period of exacerbation or remission, and may also be a complication of chronic autoimmune inflammation and/or its therapy. The myocardium, pericardium, heart valves, conducting system, large and small coronary vessels may be involved in the pathological process. . According to the results of a Russian epidemiological study conducted in 2018, 610 people per 100 thousand of the population suffer from RA. The ratio of women to men is 2-3:1. This pathology can occur in all age categories, but the peak of the development of this disease falls especially on the working age of a person – 40-55 years. This disease causes permanent disability in half of the patients suffering from this pathology during the first 3-5 years from the onset of the disease, and as a result leads to a significant reduction in the duration of their life as due to the frequent development of pathology of the cardiovascular system (CCC), various infectious diseases, oncological pathology, and specific for RA complications that are associated with systemic inflammatory process, such as rheumatoid vasculitis, amyloidosis, interstitial lung disease, etc
Keywords: chronic heart failure; rheumatoid arthritis; dyslipidemia